Fixing financial crises in the 21st century - Haldane, Andrew G. (London ; New York : Routledge, 2004)
This volume summarizes and evaluates financial crisis issues, drawing on contributions by prominent international experts in the field. it considers whether the IMF may have actually fanned the flames of future crises through its lending decisions. It assesses the contributions made by private creditors in resolving past crises - and asks what mechanisms might best be used to involve private creditors in the future.
Contributions to a conference hosted by the Bank of England in July 2002.
Includes bibliographical references and index.
aia 15/8/16
Loans
Keywords: International finance; Financial crises; 21st century financial crises